2019
DOI: 10.18632/aging.102519
|View full text |Cite|
|
Sign up to set email alerts
|

Hsa_circ_0006948 enhances cancer progression and epithelial-mesenchymal transition through the miR-490-3p/HMGA2 axis in esophageal squamous cell carcinoma

Abstract: Increasing studies have indicated that circular RNAs (circRNAs) are important in cancer progression. However, few circRNAs associated with epithelial-mesenchymal transition (EMT) have been elucidated in esophageal squamous cell carcinoma (ESCC). In this study, we aimed to identify whether hsa_circ_0006948 promotes ESCC cell EMT and explore its biological mechanisms. We first screened circRNA expression profiles using a circRNA microarray, and found that the expression of a novel circRNA, hsa_circ_0006948, is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 30 publications
2
81
0
Order By: Relevance
“…Up to now, increasing circRNAs have been discovered to be associated with the pathophysiological events in ESCC. For example, hsa_circ_0006948 was up-regulated in ESCC, and induced HMGA2 expression to facilitate ESCC progression via miR-490-3p [ 19 ]. Hsa-circ_0000654 expression was increased in ESCC tissues, and knockdown of circ_0000654 repressed cell growth and metastasis through miR-149-5p/STAT3 axis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, increasing circRNAs have been discovered to be associated with the pathophysiological events in ESCC. For example, hsa_circ_0006948 was up-regulated in ESCC, and induced HMGA2 expression to facilitate ESCC progression via miR-490-3p [ 19 ]. Hsa-circ_0000654 expression was increased in ESCC tissues, and knockdown of circ_0000654 repressed cell growth and metastasis through miR-149-5p/STAT3 axis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, circRNA is of great importance as a biomarker for cancer screening, cancer diagnosis, cancer prediction, feedback of treatment, and prognosis. Additionally, circRNA's abnormal expression and the circRNA-miRNA-mRNA regulatory network regulation have been increasingly demonstrated in a variety of tumors, such as circRNA_CAMK2A-miR-615-5p-fibronectin 1 network in lung adenocarcinoma metastasis (Du et al, 2019), circRNA_0006948-miR-490-3p-HMGA2 network in esophageal squamous cell carcinoma (Pan et al, 2019), circRNA_ACAP2-miR-29a/b-3p-COL5A1 network in breast cancer (Zhao et al, 2019), circRNA_51217-miRNA-646-TGFβ1/p-Smad2/3 network in prostate cancer (Xu et al, 2019), etc. At present, there are few reports about the circRNA-miRNA-mRNA regulatory network in GISTs.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the level of plasma circGSK3β may be a valuable predictor of recurrence/metastasis of EC [ 37 ]. Following results showed that the expressions of circ_0000654 [ 38 ], circPVT1 [ 39 ], circ_0006168 [ 40 ], circ_0004370 [ 41 ], circ-TTC17 [ 42 ], circ_0067934 [ 43 ], circ_0006948 [ 44 ], circ_0030018 [ 45 ], circ_100876 [ 46 ], circ-DLG1 [ 47 ] and circ-SLC7A5 [ 48 ] were up-regulated in EC and related to the poor prognosis of EC. However, the other group found that the expression of circ-SMAD7 in EC was significantly down-regulated and negatively correlated with tumor stage and lymph node metastasis [ 49 ], and the low expression of circ-Foxo3 was related to poor prognosis [ 50 ].…”
Section: Circrnas As Biomarkers In Ecmentioning
confidence: 99%
“…It has been found that the up-regulated expression of hsa_circ_0006948 in ESCC is related to lymph node metastasis and poor prognosis. In addition, further studies have shown that hsa_circ_0006948 promoted the proliferation, migration and invasion of through sponging miR-490-3p, and induced the formation of EMT in EC cells [ 44 ]. Similarly, it is reported that the expression of circRAD23B [ 60 ], hsa_circ_0030018 [ 45 ] and circRNA_100876 [ 46 ] in EC tissues is up-regulated, which may promote the proliferation, migration and invasion of cancer cells by activating EMT in EC [ 45 , 46 , 60 ].…”
Section: Role and Significance Of Circrnas In Ecmentioning
confidence: 99%